1980
DOI: 10.1093/ije/9.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Do Sunlight and Vitamin D Reduce the Likelihood of Colon Cancer?

Abstract: It is proposed that vitamin D is a protective factor against colon cancer. This hypothesis arose from inspection of the geographic distribution of colon cancer deaths in the U.S., which revealed that colon cancer mortality rates were highest in places where populations were exposed to the least amounts of natural light--major cities, and rural areas in high latitudes. The hypothesis is supported by a comparison of colon cancer mortality rates in areas that vary in mean daily solar radiation penetrating the atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
288
0
5

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 753 publications
(310 citation statements)
references
References 13 publications
3
288
0
5
Order By: Relevance
“…The role of vitamin D in CRC prevention was first hypothesised by Frank and Cedric Garland based on ecological studies (Garland & Garland 1980). These authors proposed that the inverse relation between solar radiation (latitude) and CRC mortality and incidence in USA might be due to vitamin D synthesis.…”
Section: 25(oh) 2 D 3 Is a Pleiotropic Hormonementioning
confidence: 99%
“…The role of vitamin D in CRC prevention was first hypothesised by Frank and Cedric Garland based on ecological studies (Garland & Garland 1980). These authors proposed that the inverse relation between solar radiation (latitude) and CRC mortality and incidence in USA might be due to vitamin D synthesis.…”
Section: 25(oh) 2 D 3 Is a Pleiotropic Hormonementioning
confidence: 99%
“…Observational epidemiological studies Garland & Garland (1980) were the first to report that CRC mortality in the United States is higher in areas where people are less exposed to natural sunlight. (Murphy et al 2012.…”
Section: Human Studies Vdr Cyp27b1 and Cyp24a1 Expressions In Cancermentioning
confidence: 99%
“…The first human evidence to suggest a relationship between vitamin D and cancer prevention came from ecologic or geographic studies which suggested increased sunlight (UVB) exposure or populations living in lower latitudes had a lower incidence of colon cancer [10], and later a reduced risk of prostate cancer [11]. Because ultraviolet radiation can lead to vitamin D formation in the skin, this led to the hypothesis that vitamin D or one of its metabolites [25(OH)D or 1,25(OH) 2 D] may be protective against cancer.…”
Section: Vitamin D and Cancer Preventionmentioning
confidence: 99%